Foreword - Martin Petrin (UCL Journal of Law and Jurisprudence, 2016)
It is with great pleasure that I write this short introduction to the latest issue of the UCL Journal of Law and Jurisprudence (UCLJLJ or the Journal). The Journal – with its brilliant team of editors, consisting of graduate students of the UCL Faculty of Laws – has always had a talent for picking timely and interesting papers. Once again, they have outdone themselves and, this time, even proven to be prescient. Earlier this year, the Journal board decided to launch the ‘City Issue’, focusing on corporate and commercial law topics that are of particular interest to the City of London and, by extension, other financial centres and jurisdictions. Given the central role of this area of law for the economy, in the UK and globally, this was already a wise choice at the time. However, after the UK’s decision to exit the EU, it would be difficult to think of a better choice of topic... for the full text please click here: http://discovery.ucl.ac.uk/id/eprint/1515925